Morphology changes upon scaling a high-efficiency, solution-processed solar cell. Issue 9 (5th August 2016) - Ro, Hyun Wook; Downing, Jonathan M.; Engmann, Sebastian; Herzing, Andrew A.; DeLongchamp, Dean M.; Richter, Lee J.; Mukherjee, Subhrangsu; Ade, Harald; Abdelsamie, Maged; Jagadamma, Lethy K.; Amassian, Aram; Liu, Yuhang; et al.
Abstract : Optimized spin-coating and blade-coating are found to produce similar performance yet notably different morphologies. Abstract : Solution processing via roll-to-roll (R2R) coating promises a low cost, low thermal budget, sustainable revolution for the production of solar cells. Poly[(5, 6-difluoro-2, 1, 3-benzothiadiazol-4, 7-diyl)- alt -(3, 3′′′-di(2-octyldodecyl)-2, 2′;5′, 2′′;5′′, 2′′′-quaterthiophen-5, 5-diyl)], PffBT4T-2OD, has recently been shown to achieve high power conversion efficiency (>10%) paired with multiple acceptors when thick films are spun-coat from hot solutions. We present detailed morphology studies of PffBT4T-2OD based bulk heterojunction films deposited by the volume manufacturing compatible techniques of blade-coating and slot-die coating. Significant aspects of the film morphology, the average crystal domain orientation and the distribution of the characteristic phase separation length scales, are remarkably different when deposited by the scalable techniques vs. spun-coat. Yet, we find that optimized blade-coated devices achieve PCE > 9.5%, nearly the same as spun-coat. These results challenge some widely accepted propositions regarding what is an optimal BHJ morphology and suggest the hypothesis that diversity in the morphology that supports high performance may be a characteristic of manufacturable systems, those that maintain performance when coated thicker than ≈200 nm. In situ measurements reveal the key differences in the solidification routes for spin- and blade-coating leading to the distinct film structures.